Unconfirmed penicillin allergy labels in the paediatric outpatient setting: A call for research and quality improvement initiatives. (16th March 2021) - Taylor, Margaret; Anvari, Sara; Palazzi, Debra
Abstract : Over the last 10 years, the electronic medical record has redefined medical documentation, and physicians rely on accurate records to make clinical decisions. Penicillin allergy labels (PALs) are important pieces of the medical history that guide physicians in selecting specific antibiotic classes for the treatment of infectious diseases. However, most children labelled as penicillin‐allergic do not have an IgE‐mediated (immediate) allergic reaction to penicillin or its derivatives. In the absence of confirmatory penicillin allergy testing or additional history, these children receive alternative, often broad‐spectrum and second‐line, antibiotics. Addressing unconfirmed PALs requires an understanding of how and why labels get added to the electronic medical record. This viewpoint highlights the knowledge gaps in paediatric outpatient penicillin allergy labelling and proposes an acronym ('LABEL') that primary care providers and antimicrobial stewards can utilise when designing initiatives to address unconfirmed PALs in the community.